2021
DOI: 10.1039/d1na00409c
|View full text |Cite
|
Sign up to set email alerts
|

Improved performance of lithium–sulfur batteries by employing a sulfonated carbon nanoparticle-modified glass fiber separator

Abstract: One of the most promising alternatives in the energy storage sector is the lithium-sulfur battery, which has a high energy density and theoretical capacity. However, the low electrical conductivity of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The cell with the MgO/PDAAQ/S revealed a small Rct value of 17.0 ohm, which did not grow as much as that of the cell with the PDAAQ/S, with a higher Rct value of 27.8 ohm after 500 cycles. The lower Rct of the MgO/PDAAQ/S cell indicates a faster ion and electron transfer at the cathode–separator interface, which is attributable to the higher contact area between the electrolyte and the conductive structure. It was found that the MgO/PDAAQ had a strong ability to capture and reuse polysulfides and allowed for fast charge and lithium-ion transport even after 500 cycles.…”
Section: Resultsmentioning
confidence: 99%
“…The cell with the MgO/PDAAQ/S revealed a small Rct value of 17.0 ohm, which did not grow as much as that of the cell with the PDAAQ/S, with a higher Rct value of 27.8 ohm after 500 cycles. The lower Rct of the MgO/PDAAQ/S cell indicates a faster ion and electron transfer at the cathode–separator interface, which is attributable to the higher contact area between the electrolyte and the conductive structure. It was found that the MgO/PDAAQ had a strong ability to capture and reuse polysulfides and allowed for fast charge and lithium-ion transport even after 500 cycles.…”
Section: Resultsmentioning
confidence: 99%
“…During the discharge process, the electrochemical reaction of the sulfur cathode involves the reaction of polysulfide intermediates with slow kinetics, which is further slowed down under harsh practical working conditions. To conquer these challenges, especially the impact of the shuttle effect on the cycle life of Li−S batteries, researchers have made numerous efforts in the design of electrode structures, modulation of the electrolyte, separator modification, and the reaction mechanism of the battery [33–38] . As one of the core inner components of the battery, the separator has been a hotspot of research by scholars.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium–sulfur (Li–S) batteries are a potential alternative to Li-ion batteries. However, there are some challenges in developing Li–S batteries, such as lower conductivity due to the insulating nature of sulfur, capacity fading, low mass loading of sulfur, and the shuttle effect. Next-generation rechargeable batteries based on zinc (Zn), magnesium (Mg), calcium (Ca), and aluminum (Al) are the most promising options. The Zn batteries can be constructed from readily available materials, are less expensive than Li-ion batteries, and have a longer service life.…”
Section: Introductionmentioning
confidence: 99%